Forests and adaptation to climate change: challenges and opportunities - Locatelli, Bruno; Brockhaus, Maria; Buck, A.; Thompson, I; Bahamondez, C.; Murdock, T.; Roberts, G.; Webbe, J. (IUFRO, 2010)
An increasing number of global, complex, interacting environmental and socio-economic drivers of change affect forests and society. This new book presents and discusses the challenges and opportunities related to the global drivers of change and the ways to reduce their adverse effects as well as to take advantage of the benefits and opportunities they might bring. The book was launched in August 2010 at the XXIII IUFRO World Congress in Seoul, Korea.